Root canal obturation with bioceramic sealer after apexification with calcium-hydroxide - Rahmiwati Rahmiwati; Ema Mulyawati (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2017)
An open apex on necrotic pulp is a common clinical cases. This condition complicates the root canal treatment by the risk of extrusion and the risk of fracture due to the thin canal walls. The aim of this case report was to describe the procedure of calcium hydroxide and bioceramic sealer use in the treatment of an open apex. A 24 years old male patient came to Oral and Dental Hospital Prof. Soedomo, Yogyakarta, Indonesia to have a treatment on his left maxillary central incisor that was injured 10 years ago. There was no pain history on the related tooth. An examination on element 21 showed an Ellis class IV fracture, fistula, discoloration, negative thermal test Chlor Ethyl (CE) and a radiolucent area around an open apex. Treatments were including apexification, bleaching, and direct composite veneer with Fiber-Reinforced-Composite post. Apexification was performed using calcium hydroxide for 3 + 3 months. After 6 months, a rather dense calcified material that was slightly shorter than the apex was observed. A checking procedure by inserting a file into the root canal showed that a hard tissue barrier had been formed. Obturation was then performed using bioceramic sealer. Bioceramic sealer was expected to strengthen the root against the risk of fracture, to continue the stimulation of tissue formation and to fill the remaining void left by apexification. Although Mineral Trioxide Aggregate (MTA) is widely use to replace calcium hydroxide, the classic material was proven to be suitable for the treatment of open apex. This is particularly useful because MTA is not always easy to obtain. ABSTRAKApeks terbuka pada nekrosis pulpa merupakan kasus klinis yang sering dijumpai. Keadaan ini menyulitkan perawatan saluran akar karena risiko ekstrusi serta risiko fraktur pada dinding saluran akar yang tipis. Tujuan laporan kasus ini adalah menunjukkan penggunaan kalsium hidroksida dan siler biokeramik untuk perawatan kasus apeks terbuka. Pasien laki-laki 24 tahun datang ke RSGM Prof. Soedomo, Yogyakarta, Indonesia untuk merawat gigi insisivus sentralis kiri maksila yang terkena benturan karena jatuh 10 tahun yang lalu. Gigi tidak pernah dirasakan sakit. Pemeriksaan pada gigi 21 menunjukkan fraktur Ellis kelas IV, fistula, diskolorasi, tes termal dengan Chlor Ethyl (CE) negatif dan area radiolusen di sekitar apeks yang terbuka. Perawatan yang dilakukan meliputi apeksifikasi, bleaching, restorasi vinir direkkomposit dengan pasak Fiber Reinforced Composite. Apeksifikasi dilakukan menggunakan kalsium hidroksida selama 3 + 3 bulan. Setelah 6 bulan gambaran radiograf menunjukkan adanya bahan terkalsifikasi agak padat yang terletak sedikit lebih pendek dari apeks. Pengecekan dengan file dalam saluran akar menunjukkan sudah adanya barrier jaringankeras. Selanjutnya obturasi dilakukan menggunakan siler biokeramik. Siler biokeramik diharapkan dapat memperkuat akar dari risiko fraktur, melanjutkan stimulasi pembentukan jaringan, serta mengisi rongga yang tidak tertutupi dengan apeksifikasi. Walaupun Mineral Trioksid Agregat (MTA) telah banyak menggantikan kalsium hidroksida, namun bahanklasik ini terbukti dapat digunakan untuk merawat apeks terbuka. Hal ini terutama bermanfaat karena MTA tidak selalu mudah didapat.